Rancang Bangun Alat Terapi Lampu Infrared dan Alat Pijat Otomatis Berbasis Arduino Uno - Halim, St. Fatimang; Saiful, Saiful (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2026)
Infrared light therapy equepment and massage equepment are tools that work to help patients who have complaints of pain in tense mus cles or pain in joints. Technology to be made in this research is the presence of safe automatic temperature control and distance sensors, it aims to reduce the risk of negligence in monitoring the duration of terapy, and can display measurement process abtained the error value the meassurement of 300 seconds / 5 minutesof 0.102%, 900 seconds /15 minutes of 0.15%. Then the process of temperature measurement at a distance of 45 cm abtained error value in the measurement of 300 seconds / 5 minutes of 0.005%. , and 900 seconds / 15 minutes by 0.002%. from that % error the module can be used. Based on the research of this tool with various developmet it can help the user to apply this tool with control automatically.